Inhibition Effect of Eco-Friendly Extract of Andrographis Paniculata on Dissolution of Aluminium in Hydrochloric Acid Medium: Evaluation of Andrographis Paniculata Extract as an Eco-Friendly Inhibitor for Aluminium Corrosion in Hydrochloric Acid Medium (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In the other side, hydrochloric acid, which is commonly used for picking, washing, descaling and etching metals, often leads to metal surface corrosion. In violent acid medium, metals suffer from extreme corrosion. Around 90 per cent of beating issues can be overcome by adding a suitable beating inhibitor into the medium. The plant extract of Andrographis paniculata have been selected to study anticorrosion on aluminum in acidic medium. The influence of the addition extract of Andrographis paniculata on the corrosion of Aluminum in 1M HCL was studied by weight loss measurement. The inhibition efficiency increases with extract concentration. The inhibitor showed maximum efficiency of 83.86 in acid at an optimum concentration of 50 ppm. The impact of the studied temperature reveals that the inhibition efficiency has decreased with rising temperature.